2015
DOI: 10.1177/0022034515598135
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocytes Directly Transform into Bone Cells in Mandibular Condyle Growth

Abstract: For decades, it has been widely accepted that hypertrophic chondrocytes undergo apoptosis prior to endochondral bone formation. However, very recent studies in long bone suggest that chondrocytes can directly transform into bone cells. Our initial in vivo characterization of condylar hypertrophic chondrocytes revealed modest numbers of apoptotic cells but high levels of antiapoptotic Bcl-2 expression, some dividing cells, and clear alkaline phosphatase activity (early bone marker). Ex vivo culture of newborn c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
125
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(140 citation statements)
references
References 23 publications
11
125
2
2
Order By: Relevance
“…While apoptosis of hypertrophic chondrocytes surely takes place, we have shown that apoptotic chondrocytes in the deepest layers of the MCC are relatively few (Jing et al 2015), casting doubt on the extent of this phenomenon. Meanwhile, estimates of the percent of hypertrophic chondrocyte-derived cells that become osteoblasts or osteocytes in limb cartilage range anywhere from 20% to 30% (Yang et al 2014a), 60% to 70% , or 80% (Yang et al 2014b), depending on the study.…”
Section: Implications For Research and Clinical Practicementioning
confidence: 77%
“…While apoptosis of hypertrophic chondrocytes surely takes place, we have shown that apoptotic chondrocytes in the deepest layers of the MCC are relatively few (Jing et al 2015), casting doubt on the extent of this phenomenon. Meanwhile, estimates of the percent of hypertrophic chondrocyte-derived cells that become osteoblasts or osteocytes in limb cartilage range anywhere from 20% to 30% (Yang et al 2014a), 60% to 70% , or 80% (Yang et al 2014b), depending on the study.…”
Section: Implications For Research and Clinical Practicementioning
confidence: 77%
“…By using the Rosa26 tdTomato lineage tracing system, our group and other investigators have shown that HCs can change their phenotype into bone cells during development [10][11][12][13][14] . Figure 1D).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, live cell imaging has been combined with lineage tracing to provide unprecedented real-time insights into progenitor cell origin and fate. In this issue, Jing et al (2015) use cell lineagetracing methods to reevaluate the current dogma concerning bone formation and reveal an unexpected fate for hypertrophic chondrocytes in mandibular condylar cartilage.It is well established that bone formation occurs by 2 distinct processes known as intramembranous and endochondral ossification. During intramembranous ossification (or dermal bone formation, as it is often called), mesenchymal cells differentiate directly into osteoblasts.…”
mentioning
confidence: 99%
“…Recently, the 605457J DRXXX10.1177/0022034515605457Journal of Dental ResearchThe Mighty Chondrocyte research-article2015 application of CRE-LOX techniques for lineage tracing, in combination with analyses of gene function in mice, has convincingly shown in vivo that not all hypertrophic chondrocytes die; instead, they can transdifferentiate directly into osteoblasts (G. Zhou et al 2014;Park et al 2015). Jing et al (2015) provide the first in vivo evidence that mandibular chondrocytes directly transform into bone cells during development of the mandible. Using 1) triple transgenic mice containing collagen I (ColI) carrying a GFP reporter (green) to follow bone progenitors (osteoblasts); 2) an inducible CRE allele under the control of aggrecan or ColX to mark chondrocytes and hypertrophic chondrocytes, respectively; and 3) Rosa 26-tomato (red) to trace chondrocytes and hypertrophic chondrocyte lineages, Jing et al reveal that most osteoblasts in the growth plate derive from the chondroblast lineage.…”
mentioning
confidence: 99%